People’s Movement to Save Sundarban for their livelihood - Uddin, Sardar Arif (Nepal Journal of Forestry, 2008)
Located in the Southern extremity of the Ganges River Delta, Sundarban with an area around half a million hectares is the world's largest mangrove forests with a rich aquatic and terrestrial biodiversity. It plays a significant role not only in the local livelihoods of South-Western region but also in the national economy of Bangladesh. About a dozen of donor-funded projects have been implemented since 1960s in and around Sundarban in natural resources sectors including forestry, water, agriculture, fishery, oil and gas. Out of them, Costal Embankment Project (1960-67), Khulna Jessore Drainage Rehabilitation Project (1995-2002), Gorai River Restoration Project (1995-2002) and Sundarban Biodiversity Conservation Project (SBCP) (2002-06) are the major projects operated in Sundarban area. The article argues that the overall impacts of the former three projects on environment, local employment and agricultural productivity were found rather negative. Therefore, a local alliance has been made among NGOs, CBOs, civil societies, journalists and local people to save Sundarban from negative project impacts and enhance sustainable environmental, social and economic benefits. The alliance also works as a 'watch group' of SBCP. The article criticizes the strategies and practices of SBCP and recommends to recognize the rights of the local people on common natural resources for sustainable management of Sundarban. Keywords: Biodiversity, Bangladesh, Sundarban, Project